Liver serine palmitoyltransferase activity deficiency in early life impairs adherens junctions and promotes tumorigenesis. Issue 6 (December 2016) - Li, Zhiqiang; Kabir, Inamul; Jiang, Hui; Zhou, Hongwen; Libien, Jenny; Zeng, Jianying; Stanek, Albert; Ou, Peiqi; Li, Kailyn R.; Zhang, Shane; Bui, Hai H.; Kuo, Ming‐Shang; et al.
Abstract : Serine palmitoyltransferase is the key enzyme in sphingolipid biosynthesis. Mice lacking serine palmitoyltransferase are embryonic lethal. We prepared liver‐specific mice deficient in the serine palmitoyltransferase long chain base subunit 2 gene using an albumin‐cyclization recombination approach and found that the deficient mice have severe jaundice. Moreover, the deficiency impairs hepatocyte polarity, attenuates liver regeneration after hepatectomy, and promotes tumorigenesis. Importantly, we show that the deficiency significantly reduces sphingomyelin but not other sphingolipids in hepatocyte plasma membrane; greatly reduces cadherin, the major protein in adherens junctions, on the membrane; and greatly induces cadherin phosphorylation, an indication of its degradation. The deficiency affects cellular distribution of β‐catenin, the central component of the canonical Wnt pathway. Furthermore, such a defect can be partially corrected by sphingomyelin supplementation in vivo and in vitro . Conclusion: The plasma membrane sphingomyelin level is one of the key factors in regulating hepatocyte polarity and tumorigenesis. (Hepatology 2016;64:2089‐2102).